Evaluasi Program Pemberdayaan Masyarakat Kelompok Ternak “Lancar Rejeki” - Beti Nur Hayati (Sociology Department Of Syiah Kuala University, 2020)
One effort to reduce poverty is to develop communities with a cross-empowerment model stakeholder. One of them is community empowerment of group